2016
DOI: 10.1021/acs.jafc.6b03966
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acid Profile and Expression of Genes Implicated in Protein Metabolism in Skeletal Muscle of Growing Pigs Fed Low-Protein Diets Supplemented with Branched-Chain Amino Acids

Abstract: Revealing the expression patterns of genes involved in protein metabolism as affected by diets would be useful for further clarifying the importance of the balance among the branched-chain amino acids (BCAAs), which include leucine (Leu), isoleucine (Ile), and valine (Val). Therefore, we used growing pigs to explore the effects of different dietary BCAA ratios on muscle protein metabolism. The Leu:Ile:Val ratio was 1:0.51:0.63 (20% crude protein, CP), 1:1:1 (17% CP), 1:0.75:0.75 (17% CP), 1:0.51:0.63 (17% CP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 79 publications
1
36
0
Order By: Relevance
“…In the present study, the concentrations of Lys, Met, Tau and total EAAs in the LD muscle were higher in the LG group than those in the L group, suggesting the FAA concentrations in the LD muscle were increased by dietary Leu and Glu supplementation. Interestingly, dietary supplementation with Leu had no effects on branch‐chain AA concentration in LD and BF muscle, which is in line with an earlier report where it was stated dietary Leu concentration increased from 1.65% to 2.35% did not impact branch‐chain AA concentration in LD muscle (Duan et al, ). Very unfortunate, the LD muscle weight was not available in the present study to elucidate the relevance between intracellular muscle FAA profile and muscle weight.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the concentrations of Lys, Met, Tau and total EAAs in the LD muscle were higher in the LG group than those in the L group, suggesting the FAA concentrations in the LD muscle were increased by dietary Leu and Glu supplementation. Interestingly, dietary supplementation with Leu had no effects on branch‐chain AA concentration in LD and BF muscle, which is in line with an earlier report where it was stated dietary Leu concentration increased from 1.65% to 2.35% did not impact branch‐chain AA concentration in LD muscle (Duan et al, ). Very unfortunate, the LD muscle weight was not available in the present study to elucidate the relevance between intracellular muscle FAA profile and muscle weight.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, reduced semitendinosus mass was associated with changes in the concentrations of Leu, Thr, Val, Met, Orn, Lys and serine (Sales, Pacheco, Blair, Kenyon, & McCoard, ). In addition, the roles of FAAs in protein synthesis in muscle were associated with changes in muscular FAA concentration (Duan et al, ), suggesting muscular FAA pools are critical to muscle protein synthesis. In the present study, the concentrations of Lys, Met, Tau and total EAAs in the LD muscle were higher in the LG group than those in the L group, suggesting the FAA concentrations in the LD muscle were increased by dietary Leu and Glu supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that a protein-restricted diet can regulate muscle and serum free AA concentrations in pigs [34][35][36]. In the present study, weaned pigs fed the 20% CP diet exhibited a significant difference in the serum free AA concentrations of Arg (P < 0.05), His (P < 0.05), Leu (P < 0.01), Val (P < 0.01), and Tyr (P < 0.05) compared with the concentrations in those fed the 14% CP diet, while Ser (P < 0.05) was significantly different between the 14% CP and 17% CP groups ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Branched‐chain amino acids (BCAAs) are abundant in the skeletal muscle and help to inhibit protein breakdown . Combined supplementation of taurine (2.0 g)–BCAA (3.2 g) attenuate eccentric elbow flexor exercise‐induced DOMS and muscle damage, which is a sign of lower LDH levels .…”
Section: Taurine's Combined Usementioning
confidence: 99%